The Effects of Monetary Change on Relative Commodity Prices and the Role of Long-Term Contracts - Bordo, Michael David (Journal of Political Economy, 1980)
The traditional explanation for the pattern of commodity price adjustment to monetary change, which stresses factors affecting the short-run elasticities of supply and demand in different markets, does not take into account price flexibility. This paper offers an explanation for the pattern of commodity price adjustment to monetary change based on differing degrees of price flexibility across industries, where price flexibility is determined by contract length. An extension to product markets of the theory of implicit long-term wage contracts leads to a simple hypothesis which explains the pattern of industry and sectoral price response to monetary change by implicit contract length, the latter being determined by relative price variability. Tests of this hypothesis across broad sectors and industries using postwar U.S. data produce favorable results. Also confirmed by the empirical evidence is the pattern of industry and sectoral price response to monetary change suggested by the tradition approach.